Parametric study of soft pneumatic robot grippers through finite element analysis - Jo, Riady S.; Ngu, Evans (IAES International Journal of Robotics and Automation (IJRA), 2024)
This paper investigates the gripping stress and deformation of pneumatically-actuated fluidic elastomer actuation (FEA)-based soft robotic gripper through ansys finite element analysis software. By varying gripper parameters, i.e. Input pressures and clearance to the object, simulations on the deformation of the soft fingers are performed to achieve gripping of the object. The motivation of this parametric study is to facilitate the design optimization of soft robotic grippers. Results demonstrate that grippers with lesser clearance to the object require lesser input pressure to achieve similar gripping stress on the object although it is evident that grippers with higher clearance are able to cater for wider range of object sizes.